(untitled) (Oratio Directa, 2019)
This study examines the influence of brand personality on Zara customer loyalty at Kota Kasablanka Mall. It applies an explanatory quantitative approach using a survey method. The population comprised 8,931 customers, while 99 respondents were selected through non-probability sampling. Data were collected using questionnaires and analyzed with SPSS 19. The findings show a correlation coefficient of 0.827, indicating a strong relationship between brand personality and customer loyalty. The regression equation produced a constant of 12.928 and a positive regression coefficient of 0.600. The coefficient of determination was 0.685, meaning that brand personality explained 68.5% of customer loyalty, while the remaining 31.5% was influenced by other variables.